2014
DOI: 10.1136/amiajnl-2014-002760
|View full text |Cite
|
Sign up to set email alerts
|

The potential for community-based health information exchange systems to reduce hospital readmissions

Abstract: Background Hospital readmissions are common, costly, and offer opportunities for utilization reduction. Electronic health information exchange (HIE) systems may help prevent readmissions by improving access to clinical data by ambulatory providers after discharge from the hospital. Objective We sought to determine the association between HIE system usage and 30-day same-cause hospital readmissions among patients who consented and participated in an operational community-wide HIE during a 6-month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 33 publications
(41 reference statements)
3
46
0
Order By: Relevance
“…; Vest et al. , ), whereas others found no link between EHRs and the two use measures (Agha ; Han et al. ; Kaushal, Edwards, and Kern ).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…; Vest et al. , ), whereas others found no link between EHRs and the two use measures (Agha ; Han et al. ; Kaushal, Edwards, and Kern ).…”
mentioning
confidence: 97%
“…; Kaushal, Edwards, and Kern ; Vest et al. ), and a few recent studies have examined the relationship between health IT use in ambulatory care settings, including EHR use and disease registries, and ACSC admissions (Han et al. ; O'Malley, Reschovsky, and Saiontz‐Martinez ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on HIE outcomes have reported modest to moderate reductions in duplicate laboratory and radiology testing [4][5][6], better identification of medication discrepancies and improved medication reconciliation [7]. HIE use has also decreased hospital readmissions and associated costs [8]. Faster access to patient information via HIE has enhanced the emergency care and reduced costs [9].…”
Section: Introductionmentioning
confidence: 99%
“…That said, HIE brings huge potential benefits for patients, clinicians, and society. HIE facilitates better and safer care for patients . It may reduce society's health care expenses—and patients’ out‐of‐pocket costs—by avoiding unnecessary diagnostic and therapeutic interventions.…”
mentioning
confidence: 99%